2011
DOI: 10.1016/j.jbi.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Use of Medical Subject Headings (MeSH) in Portuguese for categorizing web-based healthcare content

Abstract: Because of the significant results achieved by InDeCS, this tool has been successfully applied to the Brazilian healthcare search portal known as Busca Saúde. Furthermore, it could be shown that MeSH presents important results when used for the task of classifying web-based content focusing on the lay public. It was also possible to show from this study that MeSH was able to map out mutable non-deterministic characteristics of the web.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Furthermore, some participants reported that those in charge of content provision lack familiarity with MeSH C . Although these two issues are quite common when using MeSH; this has proven to be adequate in several circumstances (18)(19)(20), and the provision of support and training usually helps people to better perform in indexing information (21). Nevertheless, further investigation would be needed to evaluate the MeSH C implementation into each tool and the support provided to encoders.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some participants reported that those in charge of content provision lack familiarity with MeSH C . Although these two issues are quite common when using MeSH; this has proven to be adequate in several circumstances (18)(19)(20), and the provision of support and training usually helps people to better perform in indexing information (21). Nevertheless, further investigation would be needed to evaluate the MeSH C implementation into each tool and the support provided to encoders.…”
Section: Discussionmentioning
confidence: 99%
“…The p-values belonging to each dataset were computed to determine whether there is any meaningful difference between categories (i.e., positive, negative) in datasets (i.e., Dataset1, Dataset2) [34]. Mann-Whitney non-parametric t-test p-values of Dataset1 and Dataset2 are 0.0012 and 0.0011, respectively.…”
Section: Sentiment Analysis With Topic Extraction Using Latent Dirich...mentioning
confidence: 99%
“…They evaluate a sampling technique described by Robnik-Šikonja and Kononenko [184] and compare it with further attribute selection techniques using standard data sets. The attribute selection techniques are benchmarked [11, 16, 19, 37, 43, 49, 50, 58, 73, 85, 88-90, 97, 99, 110, 118, 119, 121, 122, 124, 127, 129, 132, 133, 155, 169, 171, 209, 215, 219, 220, 223, 244] Bayesian networks [6,16,66,75,88,122,126,133,139,150,153,210,211,246] Combined classification [6,15,28,37,39,43,52,66,74,88,89,94,97,100,109,148,153,158,171,213,220,223,226] Decision rules [6,25,52,56,61,66,91,…”
Section: Classification Techniquesmentioning
confidence: 99%